Evaluación de entendibilidad, accionabilidad y legibilidad de materiales educativos (online) en salud cardiovascular en Colombia (2021)
Cardiovascular diseases are the leading cause of death worldwide. In Colombia, 29% of annual deaths from noncommunicable diseases are due to cardiovascular diseases. With the advent of internet, there has been an increase in the availability of educational materials for patients. However, it is necessary to perform an analysis of the suitability of these educational materials for populations with varied levels of health literacy, particularly in the Colombian context. Methods: an environmental analysis was used to find the cardiovascular health materials available on the web pages of two government entities and the EPS with the largest number of affiliates. The materials were evaluated by three members of the research group independently using the educational materials quality evaluation scales (PEMAT and CCI), and software for readability analysis (INFLESZ). Results: 33 health materials were found, of which 27 met the inclusion and exclusion criteria. The analysis with the PEMAT tool showed that the materials...